AB0908 Ability of the reductive x-ray score for psoriatic arthritis (REXSPA) to detect change in an observational cohort of patients with psa. (12th June 2018) - Antony, A.; Allard, A.; Shaddick, G.; Jadon, D.; Cavill, C.; Korendowych, E.; McHugh, N.; Tillett, W.
Abstract : Background: The measurement of radiographic joint damage is important in characterising disease severity, progression, and prognosis in psoriatic arthritis (PsA). Existing radiographic measures are time-consuming to perform, leading to limited data collection from existing longitudinal observational studies. Objectives: We have previously proposed a Reductive X-ray Score for Psoriatic Arthritis (ReXSPA) 1 as more feasible method, and in this study set out to examine the sensitivity of ReXSPA in a new cohort of patients. Methods: A retrospective sample of 28 patients who had hand and feet radiographs at 3 time points (5 years before [T 0 ], at the time of [T 1 ], and 5 years post [T 2 ] commencement of anti-TNF treatment) were taken from the Bath longitudinal PsA cohort. Radiographs were scored for erosion, joint space narrowing and proliferation to calculate the Sharp-van der Heijde modified method (VDH) and ReXSPA scores. A sample of 9 radiographs were scored by all assessors (WT, AA and AA) to determine inter- and intra-rater reliability using intra-class correlation coefficients (ICC). Sensitivity to change was determined from timepoint T 0 to T 2 using the Standardised Response Mean (SRM) and Smallest Detectable Change (SDC). Results: The patients' mean age (SD) at T 0 was 61 years (13.4), the mean disease duration was 11.2 years (11.14). Patients were followed up for a mean (SD) of 10.2 years (2.76). Overall inter- and intra-rater reliability for ReXSPA and VDH were 0.80 and >0.92 and 0.91 and >0.90 respectively. The median (IQR) of ReXSPA score was 8.5 (1–14), 12.5 (5–20) and 14.5 (8–36) at T 0, T 1, and T2 respectively. The percentage SDC was 0.91 for the ReXSPA method and 0.77 for the VDH method, and the SRMs were 0.92 and 0.87 respectively (table 1), demonstrating the sensitivity of both methods in detecting change. There was a trend towards slowing in radiographic progression following the initiation of TNF-inhibitors, but ReXSPA was less sensitive compared to the VDH and was not able to detect a significant change in the rate of progression post-TNF inhibition (p 0.08) (Graphic 1). Conclusions: The RexSPA is a reliable and sensitive alternate scoring method for the detection of radiographic progression in an observational cohort of patients with PsA, but not as sensitive to change as the VDH method. Reference: [1] Tillett W, et al. (2016) Novel Composite Radiographic Score for Longitudinal Observational Studies of Psoriatic Arthritis: A Proof-of-concept Study. J Rheum; 43(2):367–370 Disclosure of Interest: None declared